Resuscitative Endovascular Balloon Occlusion of the Aorta in Inter-Hospital Transfers: Two Case Reports - Beldowicz, Brian C; Salcedo, Edgardo S; Galante, Joseph M (Journal of Endovascular Resuscitation and Trauma Management, 2018)
Non-compressible torso hemorrhage (NCTH) remains a considerable source of potentially preventable death in both military and civilian trauma. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is one tool that can be used to treat or prevent hemodynamic collapse in hemorrhaging patients suffering from NCTH, but until now its use has been mostly as a bridge to definitive hemostasis within institutions and less so as temporizing intervention in the pre-hospital setting. The cases described here are the first reported uses of REBOA as a means of enabling inter-hospital transfer within a regionalized trauma system. This experience could help inform future patient selection, procedural technique and institutional readiness to fully realize the potential for REBOA in salvaging patients with NCTH.